Photon Upconversion in Small Molecules - Dorota Bartusik-Aebisher; Mateusz Mielnik; Grzegorz Cieślar; Ewa Chodurek; Aleksandra Kawczyk-Krupka; David Aebisher (Molecules, 2022)
Upconversion (UC) is a process that describes the emission of shorter-wavelength light compared to that of the excitation source. Thus, UC is also referred to as anti-Stokes emission because the excitation wavelength is longer than the emission wavelength. UC materials are used in many fields, from electronics to medicine. The objective of using UC in medical research is to synthesize upconversion nanoparticles (UCNPs) composed of a lanthanide core with a coating of adsorbed dye that will generate fluorescence after excitation with near-infrared light to illuminate deep tissue. Emission occurs in the visible and UV range, and excitation mainly in the near-infrared spectrum. UC is observed for lanthanide ions due to the arrangement of their energy levels resulting from f-f electronic transitions. Organic compounds and transition metal ions are also able to form the UC process. Biocompatible UCNPs are designed to absorb infrared light and emit visible light in the UC process. Fluorescent dyes are adsorbed to UCNPs and employed in PDT to achieve deeper tissue effects upon irradiation with infrared light. Fluorescent UCNPs afford selectivity as they may be activated only by illumination of an area of diseased tissue, such as a tumor, with infrared light and are by themselves atoxic in the absence of infrared light. UCNP constructs can be monitored as to their location in the body and uptake by cancer cells, aiding in evaluation of exact doses required to treat the targeted cancer. In this paper, we review current research in UC studies and UCNP development.